Movies as a Teaching Tool: Enhancing Hospitality Students' Vocabulary Through Film Clips - Sri Suci Surayawati; Dewi Kurniawati; Anissa Maulinda Putri (Journal of Practice Learning and Educational Development, 2025)
Recognizing that English vocabulary often has multiple meanings and is used differently across various fields, vocabulary instruction must be adjusted to meet the specific needs of students and remain relevant to their chosen field of study. Therefore, a teacher should select an appropriate method for teaching vocabulary. This research examines the influence of movie clips on hospitality students' vocabulary mastery. It aims to determine whether the use of movie clips has a significant impact on hospitality students' vocabulary acquisition. Using a quasi-experimental design, this study employed pre-tests and post-tests as data collection techniques. The study was conducted at a Vocational High School in Bandar Lampung, involving 67 hospitality students selected from two classes, XPH 1 and XPH 2. The data was analyzed using a Paired Sample Test. The findings indicate a significant influence of movie clips on hospitality students' vocabulary mastery. The results showed that the Sig. (p-value) was < 0.001, meaning the Sig. (p-value) was less than Sig α = 0.05. This implies that Ho is rejected and Ha is accepted.These results reveal that movie clips have a significant influence on students' vocabulary mastery and can serve as an effective medium in the process of teaching and learning vocabulary.